Efficiency and Performance Analysis of the Design and Construction of a 30 Kg/Hour Coffee Grinding Machine - Franklin Taruyun Hudeardo Sinaga; Jandri Fan HT Saragi; Eka Putra Dairi Boangmanalu; Angga Bahri Pratama; Sahat Sahat (Newinera Publisher, 2026)
This study aims to evaluate the performance of a disk mill coffee grinding machine with a design capacity of 30 kg per hour for small and medium scale coffee processing. The machine was developed as a practical gasoline powered grinder to support coffee processing activities, particularly in areas where access to electricity may be limited. A performance test was conducted using roasted coffee beans with three input loads, namely 500 g, 750 g, and 1000 g. The observed parameters included grinding time, grinding capacity, product yield, residual material, material loss, material conversion efficiency, energy efficiency, and grinding quality based on particle size distribution. The results show that the machine achieved an average grinding capacity of 29.68 kg per hour, which is close to the intended capacity of 30 kg per hour. The average product yield and material conversion efficiency reached 94.55 percent, while the average material loss was 1.11 percent. However, residual material remained at 4.00 percent, indicating that the grinding chamber and discharge system still require improvement. The energy efficiency was reported at 73.8 percent, although the engine power specification needs further clarification. In terms of grinding quality, 70 percent of the particles were within the desired range of 500 to 700 micrometers. These findings indicate that the machine is technically feasible for small scale coffee production, but further refinement is needed to improve material discharge, reduce residual particles, and strengthen particle size consistency.